Predicting potential distributions of large carnivores in Kenya: An occupancy study to guide conservation. (14th June 2022) - Broekhuis, Femke; Ngene, Shadrack; Gopalaswamy, Arjun M.; Mwaura, Anastacia; Dloniak, Stephanie M.; Ngatia, Dedan K.; Tyrrell, Peter D.; Yamane, Yumi; Elliot, Nicholas B.
Abstract: Aim: Species‐specific conservation strategies are frequently formulated based on species distribution maps, which are challenging to produce, especially at large spatial scales. Our aim was to use a novel empirical approach to predict the national distribution for all six large carnivore species found in Kenya to guide conservation and management decisions by identifying knowledge and conservation gaps. Location: Kenya. Methods: We collected data on carnivore presence and absence through questionnaire and sightings‐based surveys and analysed the combined data set using single‐season false‐positive occupancy models, which account for imperfect detections and false positives. To predict potential distributions and inform conservation strategies, we used the occupancy outputs to make predictions for unsampled areas and create occupancy‐based distribution maps where ψ > 0.50, to (1) quantify differences with IUCN Red List range maps, (2) quantify overlap with wildlife areas and (3) identify areas of high carnivore richness. Results: Large carnivore occupancy was associated with land conversion, habitat and prey availability. Our results suggest that all six species are widely distributed across Kenya and reveal substantial differences to distribution maps compiled by the IUCN Red List. More specifically, our occupancy‐based distribution maps predict much larger distribution for African wild dog (5.09X), lion (4.77X) and leopard (1.46X), similar distribution for cheetah, and smaller distribution for spotted hyaena (0.84X) and striped hyaena (0.65X). For all large carnivores, the vast majority ( 80%) of their predicted distribution falls outside wildlife areas and northern Kenya is predicted to have the highest large carnivore richness. Main conclusions: Our results are encouraging as large carnivores may be widely distributed across Kenya, in some cases potentially more so than previously acknowledged. However, much of this range lies outside wildlife areas and represent areas of concern both for conservation and human livelihoods illustrating the challenges of conserving large carnivores across their range.